1990
DOI: 10.1111/j.1440-0960.1990.tb00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Do All Melanomas Come From “Moles”? A Study of the Histological Association Between Melanocytic Naevi and Melanoma

Abstract: Histological examination of 1101 melanomas (990 superficial spreading and 111 nodular melanomas) from 1098 people revealed that 23.3% showed an associated melanocytic naevus. Of these, 56.5% were classified histologically as common acquired, 37.7% as dysplastic and 5.8% as congenital. Of the superficial spreading melanomas, 25.7% showed an associated naevus. By contrast, only 2.7% of nodular melanomas showed histological evidence of a coexisting naevus. When the superficial spreading melanomas were analysed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 13 publications
7
58
1
Order By: Relevance
“…These associations seemed to largely explain initially observed associations with N+ melanoma for male sex, younger age at diagnosis, thinner melanoma, and solar elastosis in adjacent tissue. Previous studies have found, as we did, that superficial spreading melanoma was more likely than other histologic subtypes of melanoma to be N+ (19,21). In addition, many studies have reported a lower probability of finding an associated nevus with thicker melanomas (5,15,21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These associations seemed to largely explain initially observed associations with N+ melanoma for male sex, younger age at diagnosis, thinner melanoma, and solar elastosis in adjacent tissue. Previous studies have found, as we did, that superficial spreading melanoma was more likely than other histologic subtypes of melanoma to be N+ (19,21). In addition, many studies have reported a lower probability of finding an associated nevus with thicker melanomas (5,15,21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 70%
“…A hypothesis of divergent pathways has been proposed: that high cumulative sun exposure is necessary for progression of some melanomas whereas for others ''pigment cell instability,'' manifested by a propensity to develop many nevi, is sufficient to drive progression (11,17). These findings are consistent with the observation that lentigo maligna melanomas (a subtype of melanoma commonly diagnosed at sun-damaged sites) and melanomas arising on habitually sun-exposed anatomic sites are less likely to have evidence of nevus remnants than other melanomas (13,15,(18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 67%
“…Our observed prevalence of contiguous neval remnants in approximately half of all SSM but only 11% of LM/LMM is similar in magnitude to previously reported estimates. [10][11][12][13][14][15] Because of these marked differences by histologic type, we restricted further analyses to melanomas of the superficial spreading type. We found that SSM of the H & N was significantly less likely than SSM of the back to be associated with a contiguous nevus in accord with earlier descriptive studies of the anatomical distribution of nevusassociated melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,16 This could be due to earlier excision of melanomas arising in a preexisting nevus or due to the neval remnants being obscured by the growing tumor. 12,13 In our series of mainly thin melanomas, there was no evidence that the prevalence of neval remnants decreased with increasing tumor thickness. Another study of predominantly thin melanomas 11 has reported very similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, the best evidence for this association is the histological recognition of dysplastic nevi in contiguity with a melanoma, which is observed in about 20-40% of cases in most studies. [12][13][14][15][16][17] Thus, the majority of melanomas do not arise in association with a demonstrable nevus. The prevalence of dysplastic nevi is vastly greater in populations than that of melanoma, indicating, consistent with clinical observations, 18 that most dysplastic nevi are stable and do not progress to melanoma.…”
Section: Dysplastic Nevimentioning
confidence: 99%